Real-Life Data From the Largest Pediatric Familial Mediterranean Fever Cohort - Öztürk, Kübra; Coşkuner, Taner; Baglan, Esra; Sönmez, Hafize Emine; Yener, Gülçin Otar; Çakmak, Figen; Demirkan, Fatma Gül; Tanatar, Ayşe; Karadag, Serife Gül; Ozdel, Semanur; Demir, Ferhat; Çakan, Mustafa; et al. (Frontiers in Pediatrics, 2022)
Familial Mediterranean fever (FMF) is the most common monogenic autoinflammatory disease manifesting phenotypic heterogeneity. It is a clinically diagnosed disease supported by MEditerranean FeVer (MEFV) gene mutation analysis. However, the phenotype-genotype correlation is not yet established clearly. We aimed to determine the clinical findings, phenotype-genotype correlation, and treatment outcomes within a large pediatric FMF cohort. The medical charts of children with FMF who were diagnosed and followed up at the eight pediatric rheumatology units were reviewed retrospectively. All patients in the cohort were analyzed for sequence variants in exon 2,3,5 and 10 of the MEFV gene. Patients without any mutations or with polymorphisms including R202Q were excluded. A total of 3454 children were involved in the study. The mean±standard deviation of current age, age at symptom onset, and age at diagnosis were 12.1±5.2, 5.1±3.8, and 7.3±4.0 years, respectively. Of 3454 patients, 88.2% had abdominal pain, 86.7% had fever, 27.7% had arthritis, 20.2% had chest pain, 23% had myalgia and 13.1% had erysipelas-like erythema. The most common MEFV mutation patterns were homozygous (32.5%) and heterozygous (29.9%) mutations of exon 10. Homozygous M694V was present in 969 patients (28.1%). Allele frequencies of common mutations were M694V (55.3%), M680I (11.3%), V726A (7.6%), and E148Q (7.2%). Children carrying homozygous or compound heterozygous mutations had an earlier age of disease onset (4.6 vs 5.6 years, p=0.000) and a higher number of attacks per year (11.1 vs 9.6, p=0.001). Although 8% of the patients had a family history of amyloidosis, 0.3% (n=11) had the presence of amyloidosis. M694V homozygosity was detected in nine patients who developed amyloidosis. Colchicine resistance was present in 4.2% of our patients. In this largest pediatric cohort reviewed and presented to date, patients with exon 10 mutations, particularly the M694V homozygous mutation, have been demonstrated earlier disease onset, annual attack count, and more frequent colchicine-resistant cases. Although E148Q is considered a polymorphism in some populations, it was identified as a disease-causing mutation in our cohort. Secondary amyloidosis is extremely rare among children, presumably due to increased awareness, tight control, and the availability of anti-IL1 agents in colchicine-resistant cases.